Seasonal Monitoring of Glossina Species Occurrence, Infection Rates, and Trypanosoma Species Infections in Pigs in West Nile Region, Uganda - Maxamhud, Sadiya; Lindahl, Johanna F.; Mugenyi, Albert; Echodu, Richard; Waiswa, Charles; Roesel, Kristina (Vector-Borne and Zoonotic Diseases, 2022)
Trypanosomiasis is a parasitic infection caused by the protozoa Trypanosoma. It is exclusively associated with Glossina species habitats and, therefore, restricted to specific geographical settings. It affects a wide range of hosts, including humans. Animals may carry different Trypanosoma spp. while being asymptomatic. They are, therefore, potentially important in unpremeditated disease transmission. Aim: The aim of this study was to study the potential impact of the government tsetse fly control program, and to elucidate the role of pigs in the Trypanosoma epidemiology in the West Nile region in Uganda. Methods: A historically important human African trypanosomiasis (HAT) hotspot was selected, with sampling in sites with and without a government tsetse fly control program. Pigs were screened for infection with Trypanosoma and tsetse traps were deployed to monitor vector occurrence, followed by tsetse fly dissection and microscopy to establish infection rates with Trypanosoma. Pig blood samples were further analyzed to identify possible Trypanosoma infections using internal transcribed spacer (ITS)-PCR. Results: Using microscopy, Trypanosoma was detected in 0.56% (7/1262) of the sampled pigs. Using ITSPCR, 114 of 341 (33.4%) pig samples were shown to be Trypanosoma vivax positive. Of the 360 dissected tsetse flies, 13 (3.8%) were positive for Trypanosoma under the microscope. The difference in captured tsetse flies in the government intervention sites in comparison with the control sites was significant ( p < 0.05). Seasonality did not play a substantial role in the tsetse fly density ( p > 0.05). Conclusion: This study illustrated the impact of a government control program with low vector abundance in a historical HAT hotspot in Uganda. The study could not verify that pigs in the area were carriers for the causative agent for HAT, but showed a high prevalence of the animal infectious agent T. vivax.
Keywords: Trypanosoma brucei; Animal African trypanosomiasis; Nagana; Tsetse flies; Latent infection; Swine